Cranially migrated lumbar intervertebral disc herniations: A multicenter analysis with long-term outcome - Sait Ozturk; Hakan Cakin; Fatih Demir; Serdal Albayrak; Bekir Akgun; Yahya Turan; Fatih Serhat Erol; Metin Kaplan (Journal of Craniovertebral Junction and Spine, 2019)
Objective: Risk factors of cranial migration were investigated in patients with lumbar disc herniation (LDH) that migrated in the cranial direction and the long-term outcomes are discussed in this study. Materials and Methods: Patients who underwent surgery for LDH at four different centers between 2012 and 2017 were studied. Extraligamentous discs were located in the lateral part of the posterior longitudinal ligament (PLL) within the spinal canal of the axial plane, and subligamentous discs were located under the PLL. The extent of cranial migration was calculated as a percentage of the height of the migrated corpus. Based on the extent of cranial migration, partial hemilaminectomy or hemilaminectomy was performed at different rates in each patient and the amount of laminectomy performed was recorded. During surgery, all free fragments were attempted to be removed. The appropriate technique was decided intraoperatively, and the surgery was performed on an individual patient basis. Results: Of 1289 patients who underwent surgery for LDH, 654 (50.73%) had caudal migration, 576 (44.68%) had migration at the level of the disc, and 59 (4.57%) had cranial migration. Analysis of 59 patients with cranial migration according to the localization of the disc fragment revealed that 31 had extraligamentous and 28 had subligamentous fragments (P = 0.024). Conclusions: Extraligamentous intervertebral disc fragments migrate more cranially than subligamentous intervertebral fragments. The anatomy of the PLL that varies along the corpus is the main reason for the weakness of the resistance of the disc material to the dorsolateral region, direction of discrete force vectors, and orientation of the disc fragment due to torsional vertebral movements.